PROFIL PEMAHAMAN SISWA TERHADAP LUAS DAN KELILING BANGUN DATAR YANG DIGUNAKAN DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI KECERDASAN EMOSIONAL ( Penelitian Pada Kelas VII MTsN Ketanggung Ngawi Semester Genap Tahun Pelajaran 2013/2014 ) - Indayani, Sri; Kusmayadi, Tri Atmojo; Usodo, Budi (Jurnal Pembelajaran Matematika, 2015)
Abstract : Area and perimeter in plane gometry are one of the subjects in the study of mathematics in class VII of SMP / MTs. The mathematics learning system in Indonesia generally is not emphasized in solving the problem, but on procedural matters. Students are trained to memorize formulas, but less understood and mastered its application in solving a problem. This study aimed to describe the profile of students understanding of area and perimeter which are used in solving mathematical problems in terms of the level of emotional intelligence. The big difference in emotional intelligence on each student, it is possible to affect the level of student understanding. This research was conducted in class VII MTsN Ketanggung Ngawi. Research subjects consisted of 3 students were selected from the results of the questionnaire of emotional intelligence, which is one students with a high level of emotional intelligence, one students with the level of emotional intelligence is and one student with a low level of emotional intelligence. This study is a descriptive qualitative research. Data collection in this study was done by using a questionnaire, the results of the written test and interview-based tasks. The validity of the data is done by time triangulation. The main instrument in this study is the researchers themselves who aim to seek and collect data directly from the data source, and Insrument help in this research is the emotional intelligence questionnaire instruments, sheet student comprehension task, and interview guides. The results showed that students with high emotional intelligence and are entered on a relational level of understanding, and students with low entry level of emotional intelligence on the level of instrumental understanding. Keywords: student understanding, problem solving, emotional intelligence